Nano hybrid filler for anti-corrosion coating as well as synthesis and application of nano hybrid filler

By modifying and functionalizing the coupling agent on MXene/GQDs nanohybrid materials, the problem of agglomeration of coating fillers in epoxy coating is solved, and higher corrosion resistance and adhesion are achieved, which is suitable for protection in marine corrosion environments.

CN119552530APending Publication Date: 2025-03-04INST OF OCEANOLOGY - CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411767679.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the prior art, when optimizing the performance of MXene nanosheets in epoxy coatings, the prepared coating fillers still have agglomeration, which affects the anti-corrosion performance of the coating, and is particularly poor in marine corrosion environments.

Method used

The MXene/GQDs nanohybrid materials modified by coupling agent are covalently bonded by hydrothermal or solvent heat treatment, combined with functional treatment, to ensure that the nanomaterials are evenly dispersed in the coating and avoid agglomeration.

Benefits of technology

It significantly improves the adhesion and overall corrosion resistance between the coating and the metal matrix, extends the service life of the coating, and shows excellent corrosion resistance in marine corrosion environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552530A_ABST
    Figure CN119552530A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of nano-coatings, in particular to an MXene / GQDs nano-hybrid filler (coupling agent modified MXene / GQDs nano-hybrid filler) for an anti-corrosion coating, a synthesis method of the MXene / GQDs nano-hybrid filler and application of the MXene / GQDs nano-hybrid filler in the field of marine corrosion protection. According to the nano hybrid filler for the anti-corrosion coating, MXene and GQDs are hybridized and then subjected to functionalization treatment, and the weight ratio of the MXene to the GQDs is (1: 0.1)-(1: 10). The preparation process is simple, and the formed anticorrosive filler and coating are excellent in performance and expected to be applied to metal facilities such as offshore new energy facilities and railway engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano coating preparation, in particular to a MXene / GQDs nano hybrid filler (coupling agent modified MXene / GQDs nano hybrid filler) for anti-corrosion coating, a synthesis method and application in the field of marine corrosion protection. Background Art

[0002] my country's photovoltaic industry has achieved leapfrog development. By the end of July 2024, the installed capacity of solar power generation is about 740 million kilowatts, a year-on-year increase of 49.8%. The limited land resources have prompted the photovoltaic industry to develop offshore, but the marine environment is the most demanding corrosive environment, with high humidity, high salt fog, and high ultraviolet radiation. The corrosion of the metal structure of the photovoltaic bracket in this environment is significantly increased. Corrosion will reduce the structural strength of the bracket, affecting its bearing capacity and stability, thereby increasing the risk of bracket damage and collapse. In addition, corrosion will also cause the mechanical properties of the bracket to deteriorate, affecting its service life and power generation efficiency.

[0003] In this research field, uniform spraying of epoxy polymer coatings on metals is considered the most effective strategy to reduce the effects of corrosion. Epoxy coatings act as a physical barrier to prevent the penetration of corrosive media into metal structures, therefore, to obtain epoxy coatings with optimized properties, researchers uniformly add nanofillers with a layered impermeable structure in the polymer matrix. The efficiency of layered nanofillers in improving the barrier effect of the coating and increasing the penetration path of corrosive ions into the coating structure depends on their dispersion quality, functional groups, and inherent properties. Examples of two-dimensional nanofillers with layered morphology are clay, graphite, graphite, graphene oxide, graphitic carbon nitride, hexagonal boron nitride, and a new generation of nanomaterials MXene are considered to improve the corrosion resistance and mechanical strength of epoxy resins.

[0004] In order to optimize the performance of MXene nanosheets in epoxy coatings and achieve higher barrier properties and corrosion resistance, researchers have tried different approaches. One approach is based on the creation of functional groups on the surface of MXene nanosheets, such as silane, silane group additives and cerium cations as inhibitors, l-cysteine ​​and polyaniline. Another approach is the synthesis of MXene nanohybrid materials, and studies have shown the hybridization of MXene with graphene oxide, layered double hydroxides and imine-based covalent organic frameworks.

[0005] However, the coating fillers prepared by the above optimization method still have a certain degree of agglomeration in the coating, which affects the overall anti-corrosion performance of the coating.

[0006] Therefore, there is an urgent need to invent a nano-hybrid filler and coating thereof for anti-corrosion of metal structures for application in new energy fields such as offshore photovoltaics. Summary of the invention

[0007] The purpose of the present invention is to provide a MXene / GQDs nano-hybrid filler (coupling agent modified MXene / GQDs nano-hybrid filler) for anti-corrosion coating, a synthesis method and its application in the field of marine corrosion protection.

[0008] To achieve the above purpose, the present invention adopts the following technical solution:

[0009] A nano hybrid filler for an anti-corrosion coating, wherein the filler is MXene and GQDs which are hybridized and then functionalized, and the weight ratio of the MXene to the GQDs is 1:0.1 to 1:10.

[0010] A method for preparing a nano hybrid filler for an anti-corrosion coating:

[0011] Step 1, preparing GQDs powder;

[0012] Step 2, hybridization treatment of MXene nanomaterials and GQDs powders;

[0013] Step 3: functionalizing the nano-hybrid material.

[0014] Preparation of GQDs powder in step 1: citric acid, urea and deionized water are mixed and stirred in a mass ratio of 1-1.5:1-1.5:35-40, and a hydrothermal reaction is carried out at 150-180° C. for 4-6 hours. After drying, the mixture is ground to obtain a well-dispersed GQDs powder with uniform particle size.

[0015] The hybridization treatment of MXene nanomaterials and GQDs powders in step 2: MXene and GQDs are subjected to hydrothermal or solvent thermal covalent bond treatment in a high-pressure reactor at a mixing weight ratio of 1:0.5-1:5, the temperature range is 90-150°C, the treatment time is 3-15h, the thermal reaction product is centrifugally washed multiple times with deionized water and anhydrous ethanol, and then the final product is freeze-dried at -40-50°C for 24-32 hours to obtain MXene@GQDs powder.

[0016] In step 3, the nano-hybrid material is functionalized: the silane coupling agent and the MXene@GQDs powder are silane functionalized at a weight ratio of 0.1-50 (preferably 0.1-30), wherein the silane coupling agent is one or more of 3-aminopropyltriethoxysilane, 3-(2-aminoethylamino)propyltrimethoxysilane, and 3-chloropropyltrimethoxysilane.

[0017] Furthermore, the above-mentioned nano-hybrid material is added to deionized water, magnetically stirred for 20-40 minutes at room temperature and then ultrasonically dispersed for 50-60 minutes; the silane coupling agent is dispersed in toluene and stirred at room temperature; the above-mentioned two solutions are mixed and refluxed in an oil bath at 65-95°C with stirring for 8-24 hours; the material hybridization and coupling agent modification surface are selected to inhibit the oxidation of MXene and prevent the material from agglomerating in the coating matrix.

[0018] An application of the nano hybrid filler for anti-corrosion coating, and an application of the filler in the preparation of anti-corrosion coating materials in the field of marine corrosion protection.

[0019] An anti-corrosion coating material, the anti-corrosion coating is a polymer matrix and the nano-hybrid filler according to claim 1, wherein the MXene / GQDs nano-hybrid powder accounts for 0.05-3wt.% of the mass of the polymer matrix.

[0020] The polymer matrix is ​​composed of polymer resin, curing agent, auxiliary agent and solvent, the amount of the auxiliary agent added accounts for 0.1-1wt.% of the coating mass, and the anticorrosive filler is evenly dispersed in the polymer matrix.

[0021] The polymer resin is a solvent-based or water-based epoxy resin (for example, bisphenol A epoxy resins such as E44 and E51); the curing agent is an amine-based curing agent (for example, ethylenediamine, diethylenetriamine, N,N-diethylaminopropylamine and other amine curing agents); the solvent is a benzene mixture (for example, a mixture of one or more of toluene, ethylbenzene, and a xylene isomer mixture).

[0022] The auxiliary agent can be one or more of a defoamer, a leveling agent, a toughening agent, and a pigment or filler.

[0023] The materials in the above coating matrix, except GQDs, are all commercially available. MXene is Ti3C2T x Sheet material, coating ingredient ratio can be obtained according to actual needs;

[0024] A composite polymer coating is prepared by coating the coating material on the surface of a carbon steel metal substrate and drying it at room temperature for 48-72 hours to obtain a nano hybrid material coating.

[0025] An application of the anti-corrosion coating material, the anti-corrosion coating material can be widely used in metal anti-corrosion fields such as marine facilities and railway engineering.

[0026] The advantages of the present invention are:

[0027] The present invention utilizes the sufficient reactive active sites of the MXene / GQDs hybrid material modified by the coupling agent to improve the adhesion between the coating and the metal substrate, and can be evenly dispersed in the polymer matrix, thereby improving the anti-corrosion ability of the overall coating; the MXene / GQDs nano-hybrid coating of the present invention has a long service life and can be used as an anti-corrosion primer in conjunction with other coatings, and is a new type of marine anti-corrosion coating with great application value. Specifically, it is embodied in:

[0028] 1. After 50 days of electrochemical impedance spectroscopy testing, the epoxy resin coating with 0.1wt% MXene / GQDs nanohybrid material added has an impedance value 1-2 orders of magnitude higher than that of the single nanofiller composite coating, and has excellent anti-corrosion effect. Figure 4 shown.

[0029] 2. After 4 weeks of neutral salt spray test, obvious small blisters, corrosion spots and coating delamination appeared on the blank epoxy resin sample, while the corrosion and delamination products of the composite coatings with any one of APTES-MXene, APTES-GQDs and APTES-MXene@GQDs as nanofillers were significantly reduced, and the coating still had high adhesion to the metal substrate, such as Figure 5 shown. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 TEM image of GQDs provided in an embodiment of the present invention.

[0031] Figure 2 XRD pattern of MXene@GQDs provided for the implementation of the present invention.

[0032] Figure 3 Transmission electron microscopy (TEM) images of MXene@GQDs before and after functionalization modification provided for the implementation of the present invention, wherein (a) MXene@GQDs, (b) APTES-MXene@GQDs.

[0033] Figure 4 Impedance modulus graph of the coating provided for the embodiment of the present invention after immersion in 3.5wt.% sodium chloride solution for 50 days, wherein (a) blank epoxy resin coating EP, (b) silane-modified GQDs epoxy resin coating EP / APTES-GQDs, (c) silane-modified MXene epoxy resin coating EP / APTES-MXene, (d) silane-modified MXene@GQDs epoxy resin coating EP / APTES-MXene@GQDs, and (e) MXene@GQDs epoxy resin coating EP / MXene@GQDs.

[0034] Figure 54-week salt spray test diagram of the coating provided for the implementation of the present invention, wherein (a, a1) EP, (b, b1) EP / MXene@GQDs, (c, c1) EP / APTES-MXene, (d, d1) EP / APTES-GQDs, and (e, e1) EP / APTES-MXene@GQDs. DETAILED DESCRIPTION

[0035] The specific implementation modes of the present invention are further described below in conjunction with examples. It should be noted that the specific implementation modes described here are only for illustrating and explaining the present invention, and are not limited to the present invention.

[0036] The reagents used in the following examples and comparative examples are all commercially available products, as follows:

[0037] Citric acid, (Sinopharm Chemical Reagent Co., Ltd.)

[0038] Urea, (Shanghai Aladdin Biochemical Technology Co., Ltd.)

[0039] Anhydrous ethanol, (Sinopharm Chemical Reagent Co., Ltd.)

[0040] Deionized water, (Sinopharm Chemical Reagent Co., Ltd.)

[0041] MXene,(Shanghai Aladdin Biochemical Technology Co., Ltd.)

[0042] 3-(Aminopropyl)triethoxysilane (APTES), (Sinopharm Chemical Reagent Co., Ltd.)

[0043] 3-Chloropropyltrimethoxysilane, (Sinopharm Chemical Reagent Co., Ltd.)

[0044] Hydrochloric acid, (Sinopharm Chemical Reagent Co., Ltd.)

[0045] Nitric acid, (Sinopharm Chemical Reagent Co., Ltd.)

[0046] Epoxy resin, (Shandong Deyuan Epoxy Technology Co., Ltd.)

[0047] Carbon steel, (Yangxin Shengxin corrosion detection equipment specimen processing center)

[0048] The instruments used are as follows:

[0049] X-ray powder diffractometer, (XRD, Rigaku Ultima IV, Japan)

[0050] Transmission electron microscope (TEM, Yangxin Shengxin corrosion detection equipment specimen processing center)

[0051] Electrochemical workstation, (PGSTAT302N, Metrohm Autolab, The Netherlands)

[0052] Salt spray corrosion test chamber, (Yangxin Shengxin corrosion detection equipment specimen processing center)

[0053] Example 1

[0054] The synthesis method of the nano-hybrid material coating is specifically implemented in the following steps:

[0055] 1) First, the coupling agent is modified to prepare the nano-hybrid material

[0056] 1.1) GQDs synthesis: 2 g of citric acid, 2 g of urea, and 70 g of deionized water were weighed and mixed in a beaker under magnetic stirring at room temperature for 30 min, and then hydrothermally reacted at 160 °C for 4 h. After the reaction was completed, the sample was dried at 80 °C and finally ground into GQDs powder (see Figure 1 );

[0057] 1.2) Synthesis of MXene@GQDs nanohybrid materials: 10 mL of MXene solution was added to 60 mL of deionized water, followed by 0.1 g of GQDs, and stirred at room temperature for 30 min. The mixing weight ratio of MXene to GQDs was 1:1. Then, the mixture was transferred to an autoclave equipped with a polytetrafluoroethylene container and treated in an oven at 100 °C for 4 hours. The hydrothermal reaction product was washed several times by centrifugation with deionized water and anhydrous ethanol. Then, the final product was freeze-dried at -50 °C for 24 hours to obtain MXene@GQDs powder (see Figure 2 and 3 (a)).

[0058] 1.3) Coupling agent modified nanohybrid material: Add 2mL of coupling agent 3-(aminopropyl)triethoxysilane to 100mL of anhydrous ethanol, and stir magnetically at room temperature for 30 minutes to obtain a coupling agent-ethanol solution. In another beaker, dissolve 0.2g of the nanomaterial obtained in 1.2) above in 20mL of deionized water, and stir magnetically at room temperature for 30 minutes to obtain a solution containing the nanomaterial. Then add the solution containing the nanomaterial to the coupling agent-ethanol solution and stir at 80°C for 8 hours. The mixed solution is washed with deionized water and anhydrous ethanol in a centrifuge at 8000 rpm. Then, the modified nanomaterial is directly dissolved in anhydrous ethanol, and the nanomaterial is well dispersed in ethanol under strong magnetic stirring, and the concentration is measured three times;

[0059] 2) Preparation of anti-corrosion coating materials:

[0060] 100 g of epoxy resin, 20 g of curing agent and 50 g of diluent are weighed in a mass ratio to obtain a base coating. According to the above-mentioned nano-hybrid filler concentration calculation, the nano-hybrid filler is added to the base coating and evenly dispersed so that the nano-hybrid material accounts for 0.1 wt% of the mass of the base coating, thereby obtaining a nano-hybrid material coating material.

[0061] The epoxy resin used in the above preparation process is a solvent-based epoxy resin E44 modified with terminal hydroxyl polydimethylsiloxane in a conventional manner, which can be purchased commercially; the curing agent is an amine-based curing agent (polyamide resin (Zhenjiang Danbao Resin Co., Ltd.), amine value = 220 ± 20KOH / g); and the diluent is a commercially available xylene isomer mixture (thinner 91-92).

[0062] The nanocomposite coating material obtained above was brushed onto the pre-cleaned surface of the carbon steel metal substrate, dried at room temperature for 24 h, and then dried in an oven at 60° C. for 24 h to obtain a MXene@GQDs nanohybrid material coating.

[0063] Depend on Figure 1 It can be seen that the synthesized graphene quantum dots are uniform in size and are basically spherical particles, which makes them more conducive to hybridization with MXene and Figure 2 It can be seen that MXene@GQDs nanohybrid materials were successfully synthesized; Figure 3 (a, b) It can be seen that GQDs are covered on the MXene surface as uniform spherical nanomaterials. After the surface is modified with APTES, the APTES molecules are densely covered on the surface of the nanohybrid material, so that the flakes are covered with a dark color and GQDs with small particle size cannot be observed.

[0064] Example 2

[0065] The synthesis method of MXene@GQDs nanohybrid material coating is as follows:

[0066] 1) Preparation of coupling agent modified nanohybrid materials

[0067] 1.1) GQDs synthesis: 2 g of citric acid, 2 g of urea, and 70 g of deionized water were weighed, mixed in a beaker, and magnetically stirred for 30 min at room temperature, and then hydrothermally reacted at 160 ° C for 4 h. After the reaction was completed, the sample was dried at 80 ° C and finally ground into GQDs powder;

[0068] 1.2) Synthesis of MXene@GQDs nanohybrid materials: 10 mL of MXene solution was added to 60 mL of deionized water, followed by 0.1 g of GQDs, and stirred at room temperature for 30 min. The mixing weight ratio of MXene to GQDs was 1:1. Then, the mixture was transferred to an autoclave equipped with a polytetrafluoroethylene container and treated in an oven at 100 °C for 4 hours. The hydrothermal reaction product was washed several times by centrifugation with deionized water and anhydrous ethanol. Then, the final product was freeze-dried at -50 °C for 24 hours to obtain MXene@GQDs powder (see Figure 2 and 3 (a)).

[0069] 1.3) Coupling agent modified nanohybrid material: Add 2 mL of coupling agent to 100 mL of anhydrous ethanol, magnetically stir at room temperature for 30 minutes to obtain a coupling agent-ethanol solution. In another beaker, dissolve 0.2 g of the nanomaterial obtained in 1.2) above in 20 mL of deionized water, and magnetically stir at room temperature for 30 minutes to obtain a solution containing the nanomaterial. Then add the solution containing the nanomaterial to the coupling agent-ethanol solution and stir at 80°C for 8 hours. The mixed solution is washed with deionized water and anhydrous ethanol in a centrifuge at 8000 rpm. Then, the modified nanomaterial is directly dissolved in anhydrous ethanol, and the nanomaterial is well dispersed in the ethanol under strong magnetic stirring, and the concentration is measured three times;

[0070] 2) Preparation of anti-corrosion coating material: Weigh according to the mass ratio of 100g epoxy resin, 20g curing agent and 50g diluent to obtain a base coating, and add the nano-hybrid filler into the base coating and evenly disperse it according to the above-mentioned concentration calculation so that the nano-hybrid material accounts for 0.2wt% of the mass of the base coating, so as to obtain a nano-hybrid material coating material.

[0071] The epoxy resin used in the above preparation process is solvent-based epoxy resin E44; the curing agent is an amine-based curing agent (polyamide resin (Zhenjiang Danbao Resin Co., Ltd.)); the diluent is a commercially available xylene isomer mixture (thinner91-92), and the coupling agent is 3-chloropropyltrimethoxysilane.

[0072] The nanocomposite coating material obtained above was brushed onto the pre-cleaned surface of the carbon steel metal substrate, dried at room temperature for 24 h, and then dried in an oven at 60° C. for 24 h to obtain a MXene@GQDs nanohybrid material coating.

[0073] Comparative Example 1

[0074] Preparation of silane-modified GQDs epoxy resin coating material APTES-GQDs:

[0075] The surface of the GQDs nanomaterial was treated with a silane coupling agent, and APTES-GQDs were obtained by a simple chemical reaction, specifically: 2 mL of APTES (purity 98%, Aladdin Industries, China) was added to 100 mL of anhydrous ethanol and magnetically stirred at room temperature for 30 minutes. In another beaker, 0.2 g of the desired nanomaterial (the raw material GQDs in Example 1 above) was dissolved in 20 mL of deionized water and magnetically stirred at room temperature for 30 minutes. The solution containing the nanomaterial was then added to the APTES-ethanol solution and stirred at 80°C for 8 hours. The product was washed with deionized water and anhydrous ethanol in a centrifuge at 8000 rpm. Then, a portion of the modified nanomaterial was freeze-dried at -50°C for 24 hours to obtain APTES-GQDs powder for characterization test analysis;

[0076] Another part of the nanomaterials was directly dissolved in anhydrous ethanol, and the nanomaterials were well dispersed in the ethanol under strong magnetic stirring, and the concentration was measured three times. According to the description in Example 1, 100g of epoxy resin, 20g of curing agent, and 50g of diluent were weighed to obtain a base coating, and the nanofiller concentration was calculated according to the above, and added to the base coating to be uniformly dispersed so that the APTES-GQDs material accounted for 0.2wt% of the base coating mass, that is, the EP / APTES-GQDs coating material was obtained.

[0077] Comparative Example 2

[0078] Preparation of silane-modified MXene epoxy resin coating material APTES-MXene:

[0079] APTES-MXene was obtained by treating MXene nanomaterials with a silane coupling agent. 2 mL of APTES was added to 100 mL of anhydrous ethanol and magnetically stirred at room temperature for 30 minutes. In another beaker, 0.2 g of the desired nanomaterial (MXene (raw material Mxene, i.e., unfunctionalized Mxene)) was dissolved in 20 mL of deionized water and magnetically stirred at room temperature for 30 minutes. The solution containing the nanomaterial was then added to the APTES-ethanol solution, stirred at 80 ° C for 8 hours, and then washed with deionized water and anhydrous ethanol in a centrifuge at 8000 rpm. Then, a portion of the modified nanomaterial was freeze-dried at -50 ° C for 24 hours for characterization analysis.

[0080] Another part of the nanomaterials was directly dissolved in anhydrous ethanol, and the nanomaterials were well dispersed in the ethanol under strong magnetic stirring, and the concentration was measured three times. According to the description in Example 1, 100g of epoxy resin, 20g of curing agent, and 50g of diluent were weighed to obtain a base coating, and the nanofiller concentration was calculated according to the above, and added to the base coating and evenly dispersed so that the APTES-MXene material accounted for 0.2wt% of the base coating mass, that is, the EP / APTES-MXene coating material was obtained.

[0081] Comparative Example 3

[0082] To synthesize the hybrid of MXene@GQDs, MXene nanosheets were dissolved in deionized water with a concentration of 10 mg / mL and purchased from Shandong Xiyan New Material Technology Co., Ltd. GQDs synthesis: 2 g of citric acid, 2 g of urea, and 70 g of deionized water were weighed and mixed in a beaker under magnetic stirring at room temperature for 30 min, and then hydrothermally reacted at 160 °C for 4 h. After the reaction was completed, the sample was dried at 80 °C and finally ground into GQDs powder.

[0083] To this end, 10 mL of MXene solution was added to 60 mL of DI water, followed by 0.1 g of GQDs, and stirred at room temperature for 30 min. The weight ratio of MXene to GQDs was 1:1. Then, the mixture was transferred to an autoclave equipped with a polytetrafluoroethylene container and treated in an oven at a temperature of 100 ° C for 4 h. The hydrothermal reaction product was centrifugally washed several times with deionized water and anhydrous ethanol. Then, the final product was freeze-dried at -50 ° C for 24 h to obtain MXene@GQDs powder.

[0084] The coating materials prepared above were tested accordingly:

[0085] 1) Impedance modulus test: Electrochemical impedance spectroscopy (EIS) was used to measure the EIS using an electrochemical workstation (PGSTAT302N, Metrohm Autolab, The Netherlands) at 10 -2 -10 5 The steady-state open circuit potential (OCP) was recorded in the Hz frequency range with an amplitude of 10 mV. The working electrode, saturated Hg / Hg2Cl2 electrode and platinum wire were used as working electrode, reference electrode and counter electrode, respectively.

[0086] The change of impedance modulus at a frequency of 0.01Hz (│Z│0.01Hz), such as Figure 4 The impedance modulus of EP and EP / MXene@GQDs is 10 8 Ω·cm 2 After 20 days of immersion, the 5 Ω·cm2 and 10 6 Ω·cm 2 At the same time, the nanomaterials have more stable corrosion resistance to NaCl electrolyte, and the impedance value decreases at a slower rate. After immersion in NaCl electrolyte for 50 days, the impedance modulus of EP / APTES-GQDs and EP / APTES-MXene is still 10 7 Ω·cm 2 The EP / APTES-MXene@GQDs sample has the highest │Z│ value in the corrosion test, which is still as high as 10 after 50 days of immersion. 9 Ω·cm 2 , and the capacitance area of ​​this sample is significantly wider than that of other prepared coatings, indicating that the corrosion ions that penetrate into the coating structure are less. The barrier enhancement effect of the coating is EP <EP / MXene@GQDs<<EP / APTES-GQDs<EP / APTES-MXene<

[0087] EP / APTES-MXene@GQDs.

[0088] 2) Salt spray test

[0089] The coating materials obtained in the above examples and comparative examples were subjected to accelerated corrosion resistance tests using salt spray tests. The salt spray test was conducted in accordance with ASTM B-117. The experimental parameters of the salt spray chamber were: 5wt.% NaCl solution, 100% relative humidity, and salt spraying for 1 minute every 6 minutes. Figure 5 The corrosion resistance of the coating was studied by using the salt spray test.

[0090] Depend on Figure 5 It can be seen that obvious small blisters, corrosion spots and coating delamination appeared on the EP and EP / MXene@GQDs samples, which was caused by the corrosive medium entering the metal substrate through the pores and defects inside the EP coating and along the EP / substrate interface. The nanohybrid material MXene@GQDs was directly added to the coating without being modified by silane coupling agent, and obvious corrosion also occurred. It is speculated that the nanomaterial has serious agglomeration. When any of APTES-MXene, APTES-GQDs and APTES-MXene@GQDs was loaded into the EP matrix as a nanofiller, the corrosion and delamination products of the sample were significantly reduced, and after 4 weeks of salt spray test, the coating still had a high bonding performance with the steel substrate. The visual results after the salt spray test confirmed the results of EIS, indicating that the nanofiller modified by silane coupling agent has a positive effect on improving the ability of polymer coatings to resist corrosion environments.

[0091] It should be understood from the above that, under the enlightenment of the present invention, a person skilled in the art may make various changes such as substitution and simple combination without departing from the scope of protection of the claims of the present invention, and the scope of protection of the present invention shall be based on the claims.

Claims

1. A nano hybrid filler for anti-corrosion coating, characterized in that: The filler is MXene and GQDs which are hybridized and then functionalized, and the weight ratio of the MXene to the GQDs is 1:0.1 to 1:

10.

2. A method for preparing the nano hybrid filler for anti-corrosion coating according to claim 1, characterized in that: Step 1, preparing GQDs powder; Step 2, hybridization treatment of MXene nanomaterials and GQDs powders; Step 3: functionalizing the nano-hybrid material.

3. The method for preparing a nano-hybrid filler for an anti-corrosion coating according to claim 2, characterized in that: Preparation of GQDs powder in step 1: citric acid, urea and deionized water are mixed and stirred in a mass ratio of 1-1.5:1-1.5:35-40, and a hydrothermal reaction is carried out at 150-180° C. for 4-6 hours. After drying, the mixture is ground to obtain a well-dispersed GQDs powder with uniform particle size.

4. The method for preparing a nano-hybrid filler for an anti-corrosion coating according to claim 2, characterized in that: The hybridization treatment of MXene nanomaterials and GQDs powders in step 2: MXene and GQDs are subjected to hydrothermal or solvent thermal covalent bond treatment in a high-pressure reactor at a mixing weight ratio of 1:0.5-1:5, the temperature range is 90-150°C, the treatment time is 3-15h, the thermal reaction product is centrifugally washed multiple times with deionized water and anhydrous ethanol, and then the final product is freeze-dried at -40-50°C for 24-32 hours to obtain MXene@GQDs powder.

5. The method for preparing a nano-hybrid filler for an anti-corrosion coating according to claim 2, characterized in that: In the step 3, the nano-hybrid material is functionalized: the silane coupling agent and the MXene@GQDs powder are silane functionalized at a weight ratio of 0.1-50, wherein the silane coupling agent is one or more of 3-aminopropyltriethoxysilane, 3-(2-aminoethylamino)propyltrimethoxysilane, and 3-chloropropyltrimethoxysilane.

6. An application of the nano hybrid filler for anti-corrosion coating according to claim 1, characterized in that: The filler is used in preparing anti-corrosion coating materials in the field of marine corrosion protection.

7. An anti-corrosion coating material, characterized in that: The anti-corrosion coating is a polymer matrix and the nano-hybrid filler according to claim 1, wherein the MXene / GQDs nano-hybrid powder accounts for 0.05-3wt.% of the mass of the polymer matrix.

8. The anti-corrosion coating material according to claim 7, characterized in that: The polymer matrix is ​​composed of polymer resin, curing agent, auxiliary agent and solvent, the amount of the auxiliary agent added accounts for 0.1-1wt.% of the coating mass, and the anticorrosive filler is evenly dispersed in the polymer matrix.

9. A method for preparing a composite polymer coating, characterized in that: The coating material according to claim 7 is applied to the surface of a carbon steel metal substrate and dried at room temperature for 48-72 hours to obtain a nano-hybrid material coating.

10. An application of the anti-corrosion coating material according to claim 7, characterized in that: The anti-corrosion coating material can be widely used in metal anti-corrosion fields such as marine facilities and railway engineering.

Citation Information

Patent Citations

  • Graphene quantum dot / MXene nanosheet two-dimensional composite material as well as preparation method and application thereof

    CN113718281A

  • Nano hybrid material coating material as well as synthesis method and application thereof

    CN114958147A

Cited By

  • MXene modified friction response type anti-corrosion coating suitable for alcohol-based fuel ship and preparation method of MXene modified friction response type anti-corrosion coating

    CN122169082A